The Covenant and the Cross: Building on Rahner’s Soteriology - Peterson, Brandon R. (Philosophy & theology, 2024)
Rahner’s theology of the cross, as articulated in the last two decades of his life, has several weaknesses: it neglects Jesus’ Jewishness, makes supersessionist presumptions, is typically more abstruse than dramatic, and is insufficiently connected to his theology of sin. At the same time, many of his core soteriological insights remain valuable. This article seeks to expand on those insights, especially by integrating post-conciliar covenantal theologies. A soteriology which features Christ as the covenant-in-person, I argue, can serve as a corrective to these shortcomings and capitalize on Rahner’s contributions.